Human CD8 T‐stem cell memory subsets phenotypic and functional characterization are defined by expression of CD122 or CXCR3. Issue 7 (23rd April 2021) - Zhao, Yanran; Cai, Curtis; Samir, Jerome; Palgen, Jean‐Louis; Keoshkerian, Elizabeth; Li, Hui; Bull, Rowena A.; Luciani, Fabio; An, Hongyan; Lloyd, Andrew R.
Abstract: Long‐lived T‐memory stem cells (TSCM ) are key to both naturally occurring and vaccine‐conferred protection against infection. These cells are characterized by the CD45RA + CCR7 + CD95 + phenotype. Significant heterogeneity within the TSCM population is recognized, but distinguishing surface markers and functional characterization of potential subsets are lacking. Human CD8 TSCM subsets were identified in healthy subjects who had been previously exposed to CMV or Influenza (Flu) virus in flow cytometry by expression of CD122 or CXCR3, and then characterized in proliferation, multipotency, self‐renewal, and intracellular cytokine production (TNF‐α, IL‐2, IFN‐γ), together with transcriptomic profiles. The TSCM CD122 hi ‐expressing subset (versus CD122 lo ) demonstrated greater proliferation, greater multipotency, and enhanced polyfunctionality with higher frequencies of triple positive (TNF‐α, IL‐2, IFN‐γ) cytokine‐producing cells upon exposure to recall antigen. The TSCM CXCR3 lo subpopulation also had increased proliferation and polyfunctional cytokine production. Transcriptomic analysis further showed that the TSCM CD122 hi population had increased expression of activation and homing molecules, such as Ccr6, Cxcr6, Il12rb, and Il18rap, and downregulated cell proliferation inhibitors, S100A8 and S100A9. These data reveal that the TSCM CD122 hi phenotype is associated with increased proliferation, enhanced multipotency and polyfunctionality with an activated memory‐cell like transcriptional profile, and hence, may be favored for induction by immunization and for adoptive immunotherapy. Abstract :